Empirical evaluation of change in crash risk due to lane marking reallocation: A case study in Kochi City, Japan - Hiroaki Nishiuchi; Charitha Dias; Satsuki Kawato (IATSS Research, 2023)
Lane markings are considered an essential component of a road system. As highlighted in previous studies, they are directly linked to efficiency and safety. The rearrangement or reallocation of lane markings can be an economical way to improve efficiency. However, such changes could influence driver behavior. Thus, there is a tradeoff between efficiency and safety. Through a case study in Kochi City, Japan, this study evaluated the change in crash risk caused by a lane marking reallocation. Video data were collected before and after the implementation of a new road layout (achieved by reallocating lane markings) that was intended to mitigate traffic congestion at a signalized intersection. Based on the video data, PICUD (Possibility Index for Collision with Urgent Deceleration), a surrogate safety index used to estimate collision risk, was estimated for lane changes and conflicts between leading and following vehicles in the through lane. In particular, it was confirmed that the collision risk between a lane-changing vehicle and a leading vehicle in the through lane was reduced due to the reduction in traffic density caused by the new road layout. In addition, the results indicate that the PICUD value tends to decrease (i.e., the crash risk tends to increase) with increasing speed of the following vehicle relative to the leading vehicle. Overall, the improvement in safety after the implementation of the new road layout was marginal and statistically insignificant. Therefore, this study highlights the necessity of incorporating speed control measures, such as speed limits, along with congestion alleviation measures in order to enhance safety.